Lone witness eaudiobook Atlanta justice series, book 2. - Dylan, Rachel (Atlanta Justice, 2018)
Prosecutor Sophie Dawson's first job in the White Collar division of the Fulton County D.A.'s office is to build a case against a local bank employee who may be cheating clients. But when circumstances beyond her control leave her as the only witness to a double homicide involving a vengeful gang, her world is turned upside down. Former Atlanta police officer turned private security guard Cooper Knight is hired to ensure that Sophie is kept safe. But as threats escalate, they don't know who they can trust. Sophie is determined not to back down, but her bank case gets more complicated by the day, and the gang will stop at nothing to keep her from testifying. Sophie wants to take a stand for what's right—but can Cooper, who is determined not to be distracted by their growing attraction, keep her safe so that she can finish her pursuit for justice?